2009
DOI: 10.4269/ajtmh.2009.09-0070
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Pattern of Pneumonia Mortality among Under-Five Children in Nairobi’s Informal Settlements

Abstract: Abstract. Using longitudinal data from the Nairobi Urban and Demographic Surveillance System (NUHDSS), we examined the seasonal pattern of pneumonia mortality among under-five children living in Nairobi's slums. We included 17,787 under-five children resident in the NUHDSS from January 1, 2003 to December 31, 2005 in the analysis. Four hundred thirty-six deaths were observed and cause of death was ascertained by verbal autopsy for 377 of these deaths. Using Poisson regression, we modeled the quarterly mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 32 publications
2
24
1
1
Order By: Relevance
“…In addition, time-series studies on respiratory mortality have suggested that temperature has lag effects up to 3 weeks after exposure 14. As one of the major respiratory diseases, pneumonia has been reported to be influenced by meteorological factors 11 1517. However, the relationships varied across areas with different weather patterns and latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, time-series studies on respiratory mortality have suggested that temperature has lag effects up to 3 weeks after exposure 14. As one of the major respiratory diseases, pneumonia has been reported to be influenced by meteorological factors 11 1517. However, the relationships varied across areas with different weather patterns and latitudes.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these deaths occur in the tropics, where pneumonia in children occurs most commonly in the rainy season [2][3][4] . The mechanisms underlying this seasonality are unknown but possibilities include increased pathogen survival or stability in aerosols (possibly due to variations in temperature, humidity or sunlight), reduced host immunity (possibly due to variations in nutrition, sunlight, or co-infections) and increased host mixing due to seasonal variations in behavioural patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The approach has been used to determine CODs among people of all ages in a wide range of settings (2, 7, 9–16); however, in Kenya, although VAs have been widely used as a tool for documenting CODs (7, 1214, 1721) , no study has yet been published in which the WHO-compliant InterVA-4 has been applied across deaths of all ages. The InterVA-4 model uses posterior probabilities for CODs, given an a priori distribution of CODs in the population and conditional probabilities for circumstances leading to death.…”
mentioning
confidence: 99%